Using Alsace‐Moselle Local Laws to Build a Difference‐in‐Differences Estimation Strategy of the Employment Effects of the 35‐Hour Workweek Regulation in France - Chemin, Matthieu; Wasmer, Etienne (Journal of Labor Economics, 2009)
France’s 1998 implementation of the 35‐hour workweek has been one of the greatest regulatory shocks on labor markets. Few studies evaluate the impact of this regulation because of a lack of identification strategies. For historical reasons due to the way Alsace‐Moselle was returned to France in 1918, the implementation of France’s 35‐hour workweek was less stringent in that region than in the rest of the country, which is confirmed by double and triple differences. Yet it shows no significant difference in employment with the rest of France, which casts doubt on the effectiveness of this regulation.